2021
DOI: 10.1016/j.jesf.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sprint distance and repetition number on energy system contributions in soccer players

Abstract: Background/objective This study aims to compare the effect of sprint distance and repetition number on performance, physiological responses, and energy systems contributions. Methods Eighteen male university league soccer players (age: 19.9 ± 1.6 years, height: 177.9 ± 4.7 cm, body mass: 72.4 ± 6.3 kg, percentage body fat: 8.9 ± 1.8, training experience: 7.4 ± 1.6 years) completed two different repeated sprint protocols: 20 × 20 m (20 × 20) and 10 × 40 m (10 × 40) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
0
23
0
8
Order By: Relevance
“…One possible reason could be linked to rest intervals. While resistance training studies include efforts with a usual 90 s rest between "all-out" sets, sprints protocols used 35 seconds, which could modify energetic dynamic contributions (Neufer, 2018;Ulupınar et al, 2021). Other reason could be related to discomfort of capsaicin supplementation intake in gastrointestinal tract reported in the cited study where 13.5% of participants of withdraw before the end (Opheim & Rankin, 2012).…”
Section: Supplementation and High Intensity Interval Trainingmentioning
confidence: 99%
“…One possible reason could be linked to rest intervals. While resistance training studies include efforts with a usual 90 s rest between "all-out" sets, sprints protocols used 35 seconds, which could modify energetic dynamic contributions (Neufer, 2018;Ulupınar et al, 2021). Other reason could be related to discomfort of capsaicin supplementation intake in gastrointestinal tract reported in the cited study where 13.5% of participants of withdraw before the end (Opheim & Rankin, 2012).…”
Section: Supplementation and High Intensity Interval Trainingmentioning
confidence: 99%
“…Recent studies have revealed that sprint distance differs in energy metabolism in repeated sprint protocols. Two studies with a similar design showed more anaerobic glycolysis activity in 30-meter sprints than in 15-meter sprints (88) and in 40-meter sprints than in 20-meter sprints (89). These studies revealed that prolonging the single sprint distance can cause more lactate production even if the total distance is equal.…”
Section: Discussionmentioning
confidence: 97%
“…Scientific findings showed that training improves V̇O 2 kinetics during the fast phase of excess postexercise oxygen consumption (EPOC) and V̇O 2max (35,86,89). Complex physiological factors such as muscle fiber-type characteristics, mitochondrial density, oxidative enzyme activity, oxygen availability, capillary density, and muscle perfusion have the potential to reorganize V̇O 2 kinetics (11–13,35).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations